(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the health associated life quality in adults with Diabetes Mellitus, relating the domains Satisfaction, Impact, Social and Diabetes related Concerns. Methods: Transversal observational research, explanatory and analytic. The data collection was performed from July to December of 2018. This study population was constituted by 360 diabetic adults cared in the Endocrinology Ambulatory of the Fortaleza General Hospital (HGF) aged between 20 and 59 years old, of both sexes, and with both type I and type II Diabetes. Results: The major part of the interviewed people had shown to be unsatisfied with their sex life, and with their time spent on physical activities, they also suffer with low self-esteem, and they’re worried with the possibility of a denial of health or financial insurance and with complications Diabetes related. Conclusion: It has been established that these individuals’ mental health is strongly affected by the stigma of having Diabetes Mellitus, lowing their life quality. Furthermore, most of the participants have a low-income, what reduces their chance of preventing complications of the disease by adopting healthier life habits. Therefore, this issue requires a stronger government action to guarantee food security, mental health, and keeping of the care to this population.